KARAKTERISTIK BAHAN PAKAN LOKAL DI SULAWESI TENGGARA - Nuraini, Nuraini; Hafid, Harapin; Inderawati, Inderawati (FAPETKAN UNTAD, 2016)
Lower beef cattle productivity in South-East Sulawesi caused by the lack of knowledge and skill of farmers to utilize existing feed resources. This research specific objectives : (1). to identify local feed of beef cattle in South-East Sulawesi, (2) to formulate local feed become the complete rations for fattening, (3) to analyse the nutrient value of available feeds resources. This research was applied through a survey to identify local feed at eight districts andtwo cities in South-East Sulawesi, namely Kendari and Bau-bau cities, districts of Konawe South, Konawe, Bombana, Kolaka, Muna, and Buton. The Research was conducted from April to November 2007. The Laboratory analysis was conducted to know nutrient value of feed, and thus can be determined the local feed feasibility for being the ration formulation. The research result indicated that: (1) the local feed which can be identified consist of 30 types coming from waste of agriculture, plantation, industry, market and household, (2) the local feed which was available in big supply and had potency to be processed as complete ration for fattening beef cattle were cacao pods, sago waste, tofu waste, paddy bran and yellow corn, (3) the analysis of some local feed for beef cattle showing a quite higj nutrient value with the range of protein content around 2 - 9% as well as total digestible nutrient approximately 15 - 90%. The other content of nutrient and mineral was also sufficient for supporting the livestock growth.Key words: Identification, local feed, nutrient value